Prevalencia e impacto de la violencia íntima de pareja en mujres con lupus eritematoso sistémico - Campos Tinajero, Emmanuel; Ortiz Nuño, Maria Fernanda; Flores Gutierrez, Diana Paola; Esquivel Valerio, Jorge Antonio; Serna Peña, Griselda; García Arellano, Gisela; Cárdenas de la Garza, J. A.; Galarza Delgado, Dionicio Ángel; Villarreal Alarcón, Miguel Ángel; Aguilar Rivera, Estefania (2023)
Objective: Stress and trauma are psychosocial factors with an impact on the course of systemic lupus erythematosus (SLE). The influence of violence on SLE has not been entirely explored, even though women (including patients with rheumatic diseases) are a vulnerable population to any form of violence. This study aims to assess the prevalence and impact of intimate partner violence (IPV) on healthrelated quality of life in women with SLE. Methods: An observational, cross-sectional, and analytical study was conducted at a rheumatology clinic of a university hospital from September 2022 and September 2023. We evaluated the presence of IPV in 85 women with SLE with the Hurt, Insulted, Threatened with Harm and Screamed at (HITS) questionnaire and the Index of Spouse Abuse (ISA), and quality of life with LupusQoL. Results: The prevalence by HITS score of past-year IPV was 24.4% and of lifetime IPV was 36.5%. Past-year non-physical violence was present in 17.1% of patients by ISA, and 27.1% were victims in their lifetime. While in physical violence, 7.3% were victims in the previous year and 21.2% in their lifetime. The total quality of life and the emotional domain by LupusQoL were diminished in victims of past-year IPV, compared to those who weren’t exposed (p = 0.018 and p = 0.036, respectively). Past-year HITS score correlated with the physician global assessment (PGA) (rho = 0.301, p = 0.006), while lifetime HITS score correlated with PGA (rho = 0.329, p = 0.002) and SLEDAI-2K (rho = 0.277, p = 0.010). Conclusion: We found that 1 in 4 women suffered IPV in the previous year, and those who were exposed had diminished quality of life. Also, the severity of the abuse correlated with disease activity. The findings of this study highlight the relevance of assessing psychosocial factors in these patients to achieve better comprehensive care.